Application of General Principles of Good Governance in Law No. 30 of 2014 as Guidelines in Implementing the Authority of Discretion by Government Officials in Indonesia - Najicha, Fatma Ulfatun (VJJ, 2021)
This research was conducted with the aim to find out how the discretionary authority of Government officials based on Law No. 30 of 2014 concerning Government Administration and how the Implementation of General Principles of Good Governance (AUPB) within the discretionary authority of Government officials based on Law No. 30 of 2014 concerning Government Administration. By using the normative juridical research method, it is concluded: 1. Discretion is a decision or action determined or carried out by a government official to overcome concrete problems encountered in the administration of government in terms of laws and regulations that provide choice, not regulate , incomplete, or not clear, or government stagnation. In accordance with Law No. 30 of 2014 concerning Government Administration for its use discretion is used primarily because; first, an emergency that makes it impossible to apply written provisions; second, there are no or no regulations goingverning it; third, there are rules but they are vague or multiple interpretations. Freedom of discretion is freedom of administration which includes freedom of administration (interpretatieverijheid), freedom of consideration (beoordelingsvrijheid), and freedom to take policy (beleidsvrijheid). 2. General Principles of Good Governance is a way that directs and maintains the use of government authority in order to remain controlled from the abuse of power of government officials. This shows that the legal relationship between discretionary authority and General Principles of Good Governance (AUPB) is the General Principles of the Government.